Analisis Jumlah Penawaran dan Nilai Jual Buah Lokal dan Impor di Pasar Tradisional Kota Medan - Aflahun Fadhly Siregar; Salsabila Salsabila; Ade Firmansyah Tanjung (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The consumption needs of the Indonesian population for fruits is quite high but cannot be balanced with the low national fruit production so that market needs are not fulfilled. When compared with local fruits in Indonesia, the level of demand for imported fruit is higher and much in demand by consumers because of the relatively cheaper price, maintained quality and in accordance with the wishes of consumers. The objective of this research is to analyze the number of local and imported fruit supplying which supplied by retailers, analyze the selling value of local fruits and imports offered, analyze the influence of selling prices on the supply of local fruits and imported fruits by retailers of fruit in the traditional market of Medan City. The analysis method used is a simple linear regression model. Data collection method through the dissemination of questionnaires and interview techniques to local and import fruit retailers in the traditional market of Medan. The results of the study obtained that the average number of local fruit supply was as much as 132 kg/day while imported fruit as much as 23 kg/day. The selling value of local fruit was higher than imported fruit which was Rp 2,126,340/day and Rp 1,520,840/day. The selling value of local fruit was higher than imported fruit which was Rp 2,126,340/day and Rp 1,520,840/day. Based on the results of the analysis, the selling price positively influenced the local fruit supplying with a significance value of 0.042 (<0.05). Similarly, the selling price of imported fruit has a positive effect on the offer of imported fruit with a significance of 0.002 (<0.05).